2022
DOI: 10.1007/s00392-022-01996-2
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative effectiveness and safety of non-vitamin K antagonists for atrial fibrillation in clinical practice: GLORIA-AF Registry

Abstract: Background and purpose Prospectively collected data comparing the safety and effectiveness of individual non-vitamin K antagonists (NOACs) are lacking. Our objective was to directly compare the effectiveness and safety of NOACs in patients with newly diagnosed atrial fibrillation (AF). Methods In GLORIA-AF, a large, prospective, global registry program, consecutive patients with newly diagnosed AF were followed for 3 years. The comparative analyses for (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…The primary papers from GLORIA-AF Phase III registry comparing the different anticoagulation strategies have recently been published. 21 , 22 …”
Section: Methodsmentioning
confidence: 99%
“…The primary papers from GLORIA-AF Phase III registry comparing the different anticoagulation strategies have recently been published. 21 , 22 …”
Section: Methodsmentioning
confidence: 99%
“…Complete details on the design of the GLORIA-AF study have been previously reported, 20,21 as well as the primary papers comparing dabigatran versus VKA and other NOACs. 22,23 Briefly, patients with new-onset nonvalvular AF and CHA 2 DS 2 -VASc score !1 were consecutively enrolled between 2011 and 2016 (2011-2014 for phase II, and 2014-2016 for phase III). Patients enrolled in phase II who initiated dabigatran were prospectively followed up for 2 years, while all patients enrolled in phase III (irrespective of the antithrombotic treatment) were followed up for 3 years.…”
Section: Methodsmentioning
confidence: 99%
“…The GLORIA-AF is a prospective, multicentre and international registry programme structured in three phases, aimed to assess the long-term real-world safety and efficacy of dabigatran etexilate in patients with AF. Details on the design, follow-up and primary results of GLORIA-AF registry have been previously reported [ 16 19 ]. Briefly, during the study period (2011–2014 for phase II and 2014–2016 for phase III), patients (≥18 years old) with a recent diagnosis of non-valvular AF (i.e.…”
Section: Methodsmentioning
confidence: 99%